Exploring the citizens' engagement and interaction of volunteer smarpthone patrol (vsp) adoption in crime prevention of Royal Malaysia Police (RMP) law enforcement / Ghazila Ghazi - Ghazi, Ghazila (2023)
This qualitative study focused on the engagement and interaction of Volunteer Smartphone Patrol (VSP) adoption in crime prevention of Royal Malaysia Police(RMP) law enforcement. This research posits through four research objectives namely;(1) to ascertain how the adoption of VSP app contributes to the engagement and interaction between citizens and RMP in community policing, (2) to determine the reasons why RMP utilizes VSP app in law enforcement, (3) to discover how does RMP manages VSP app for crime investigation, and (4) to explore how does VSP app impacts crime prevention of RMP law enforcement. Two theories were utilized to guide this research; (i) Community Engagement Theory, and (ii) Technology Acceptance Model. Using case study design, salient discoveries were obtained through in-depth interviews with 13 informants comprises of 8 VSP Users and 5 VSP Enforcers residing in Klang Valley.